Catastrophic Limestone Decay at the Central Sanctuary of Iupiter Dolichenus at Dülük Baba Tepesi in Southern Turkey: Causes and Implications for Future Conservation. (2nd January 2017) - Wilhelm, Katrin; Viles, Heather; Winter, Engelbert; Burke, Órlaith; Engelstaedter, Sebastian; Coyte, Katharine Z.
Abstract : Dramatic deterioration of Hellenistic-Roman limestone remains recently excavated at Dülük Baba Tepesi (Southern Turkey) has been observed following the cold, wet winter of 2011/2012. A conceptual model is presented to explain the dramatic deterioration in which case hardening develops and initially strengthens the stone against deterioration, but then makes it more prone to exfoliation and blistering. Data collected using non-destructive techniques (Equotip surface hardness tester and Karsten tube for water uptake) on Fırat and Gaziantep formation limestone time series excavated in 2005, 2007, and 2013 demonstrates the progress of case hardening and deterioration after excavation. In combination with meteorological data from Gaziantep weather station the results are used to test and revise the model taking into account non-linear and threshold effects. Future excavation and conservation efforts should take into account the often-complex interactions between post-excavation case hardening and extreme winter conditions which can cause catastrophic deterioration.